‘Et in Arcadia ego’ : modulations mélancoliques de la tradition pastorale entre Lumières et Romantismes - Jean-Louis Haquette (Etudes Epistémè)
The aim of this paper is to study the modulations of the links established between pastoral and melancholy in a series of late eighteenth-century literary texts. Starting from the three definitions of « mélancolie » given in the Encyclopédie, the paper first examines eighteenth centuries interpretations of the celebrated « Shepherds of Arcady » by Poussin. They converge in distorting the visual elements of the paintings, as if the encounter between pastoral and melancholy could only be oxymorous. Turning then to prose fiction, the same motive, a tomb in the pastoral locus amoenus, is found both in Marmontel’s Palemon and Pierre Blanchard’s Felix et Pauline ; yet the confrontation between the pastoral world and melancholy is given divergent meanings, the latter narrative putting the stress on « noire mélancolie », the former on « douce mélancolie ». This pastoral encounter with melancholy is anticipated in Gray’s Elegy, which is here shown to combine innovative synthesis elements from Warton’s Pleasures of melancholy and from the Pastoral Eclogues by the same. A further modulation is then examined, which transforms the tomb into the ruins of a cottage, and introduces a new character : the wandering poet. Two examples are considered : Bernardin de Saint-Pierre’s Paul et Virginie and Wordworth’s The Ruined Cottage. All the texts considered stress the nostalgia of a lost happiness which can only be partly recovered in narration. Recombining traditional elements of earlier pastoral poetry, but giving them new expression, they establish what could be termed a « pastoralization » of melancholy, which loses its violence to become, to borrow Panofsky’s words on Poussin’s painting, « a contemplative absorption in the idea of mortality ».